2015
DOI: 10.1017/jfm.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-ratio effects on rotating wings: circulation and forces

Abstract: We employ experiments to study aspect ratio (A) effects on the vortex structure, circulation and lift force for flat-plate wings rotating from rest at 45 • angle of attack, which represents a simplified hovering-wing half-stroke. We use the time-varying, volumetric A = 2 data of Carr et al. (Exp. Fluids, vol. 54, 2013, pp. 1-26), reconstructed from phase-locked, phase-averaged stereoscopic digital particle image velocimetry (S-DPIV), and an A = 4 volumetric data set matching the span-based Reynolds number (Re)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 36 publications
10
65
1
Order By: Relevance
“…As t becomes large, the r 4/3 power law becomes dominant. Similar trends were found in the experiments by Carr et al (2015).…”
Section: Detached Vorticessupporting
confidence: 89%
See 2 more Smart Citations
“…As t becomes large, the r 4/3 power law becomes dominant. Similar trends were found in the experiments by Carr et al (2015).…”
Section: Detached Vorticessupporting
confidence: 89%
“…In PIV experiments as well as in numerical simulations, the circulation is usually calculated by summing up the spanwise vorticity contained in flat rectangular windows, cf. Carr et al (2015). Therefore, in this example, we also use flat windows of hight c and width 0.5r, shown as gray shaded areas in figure 3(a).…”
Section: Comparison Between the Analytical And The Numerical Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the extent of this stable region is not significantly reduced with respect to its extent at φ = 60 • . As such, the flow seems to have reached a limit cycle at φ = 120 • , which is consistent with previous experimental and numerical studies (Carr et al 2015;Percin & van Oudheusden 2015;Jardin & David 2017). The flow fields at φ = 120 • , 150 • and 180 • exhibit roughly similar patterns with (i) an unsteady outboard region and (ii) a quasi-steady inboard region.…”
Section: Baseline Casesupporting
confidence: 89%
“…They observed that the higher aspect-ratio wing showed a steeper growth in lift coefficient with increasing angle of attack. In another experimental study, Carr et al [8] investigated the rotating rectangular wings with AR=2 and 4 at AoA= 45 . An arch-shaped LEV was observed and found detaching from the wing surface outboard in both cases.…”
Section: Introductionmentioning
confidence: 99%